Azorean macroalgae (Petalonia binghamiae, Halopteris scoparia and Osmundea pinnatifida) bioprospection: a study of fatty acid profiles and bioactivity. (4th November 2018) - Campos, Ana M.; Matos, Joana; Afonso, Cláudia; Gomes, Romina; Bandarra, Narcisa M.; Cardoso, Carlos
Summary: The Azorean macroalgae Petalonia binghamiae, Halopteris scoparia and Osmundea pinnatifida are undervalued and require further study regarding their potential use as food. These three seaweed species had low fat contents, and their fatty acid (FA) profiles were characterised by a high proportion of saturated FA (SFA) in the case of O. pinnatifida and similar weights of SFA and polyunsaturated FA (PUFA) in the other two species. Within the PUFAs, the ω3 PUFAs were the most prominent in O. pinnatifida and P. binghamiae, yielding ω3/ω6 ratios that were higher than one. Eicosapentaenoic acid (EPA, 20:5 ω3) was the most important ω3 PUFA (10–14%). Regarding the other bioactive compounds, the polyphenols were found to reach non‐negligible levels (140–220 mg/100 g dw). Significant antioxidant activity was detected. Ethanolic extracts of H. scoparia and aqueous extracts of P. binghamiae showed cyclooxygenase‐2 (COX‐2) inhibitory capacities between 40% and 79%, indicating anti‐inflammatory activity. Abstract : Results showed that while EPA was the most abundant w3 PUFA in P. binghamiae & O. pinnatifida (10–14%), polyphenols reached 140–220 mg/100 g dw. ABTS showed antioxidant activity in aqueous extracts of H. scoparia & P. binghamiae . Regarding anti‐inflammatory activity, ethanol extract of H. scoparia showed the highest cyclooxygenase‐2‐inhibition, 79%. Accordingly, H. scoparia and P. binghamiae present significant potential for future nutreceutical and biotechnological applications.